Going to Extremes: Politics after Financial Crisis, 1870-2014 - Manuel Funke; Moritz Schularick; Christoph Trebesch (Center for Economic Studies and ifo Institute (CESifo), 2015)
Partisan conflict and policy uncertainty are frequently invoked as factors contributing to slow post-crisis recoveries. Recent events in Europe provide ample evidence that the political aftershocks of financial crises can be severe. In this paper we study the political fall-out from systemic financial crises over the past 140 years. We construct a new long-run dataset covering 20 advanced economies and more than 800 general elections. Our key finding is that policy uncertainty rises strongly after financial crises as government majorities shrink and polarization rises. After a crisis, voters seem to be particularly attracted to the political rhetoric of the extreme right, which often attributes blame to minorities or foreigners. On average, far-right parties increase their vote share by 30% after a financial crisis. Importantly, we do not observe similar political dynamics in normal recessions or after severe macroeconomic shocks that are not financial in nature.
Keywords: D72; G01; E44; 330; financial crises; economic voting; polarization; policy uncertainty